Generalised stacking fault energies of copper alloys - density functional theory calculations - Muzyk M.; Kurzydłowski K.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Generalised stacking fault energies of copper alloys have been calculated using density functional theory. Stacking fault energy of copper alloys is correlated with the d–electrons number of transition metal alloying element. The tendency to twiningis also modified by the presence of alloying element in the deformation plane. The results suggest that Cu –transition metal alloys with such elements as Cr, Mo, W, Mn, Re are expected to exhibit great work hardening rate due to the tendency to emission of the partial dislocations.